Monitoring the Melting of Snow Stored in Snow Dumps (Yuzhno-Sakhalinsk, Russia) - Valentina Lobkina; Aleksandra Muzychenko (Geosciences)
This study reviews the melting rate of anthropogenic snow patches formed as a result of cleaning the territory of Yuzhno-Sakhalinsk city from snow and collecting it in designated areas known as snow dumps. Snow patches persisted at absolute altitudes of less than 50 m in the summers during the period of 2010–2022, except in 2017. The positive factor was the ratio of the relatively small area occupied by the anthropogenic snow patch and its significant height at the beginning of the melting period. The detailed observations of anthropogenic snow patch growth and melting were conducted by the authors starting in the winter season of 2017–2018. The snow volume collected in snow dumps during the winter season in Yuzhno-Sakhalinsk can reach 3000 m3. That is why it is necessary to determine how the anthropogenic snow patch will loosen the water through the warm season. Special models of anthropogenic snow patch melting do not exist. So, the authors review the ability of four glacier and snow cover melting model applications for such objects. The contribution of various parameters affecting the snow path melting rate was also determined. The collected factual data allowed for the development of empirical snow patch melting models. The largest errors resulting in the usage of reviewed models are related to the beginning (April) and ending (September–October) of the melting periods.